2017
DOI: 10.1016/j.tranon.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Genomic Analysis in Differentiating Synchronous and Metachronous Lung Adenocarcinomas from Primary Adenocarcinomas with Intrapulmonary Metastasis

Abstract: Distinguishing synchronous and metachronous primary lung adenocarcinomas from adenocarcinomas with intrapulmonary metastasis is essential for optimal patient management. In this study, multiple lung adenocarcinomas occurring in the same patient were evaluated using comprehensive histopathologic evaluation supplemented with molecular analysis. The cohort included 18 patients with a total of 52 lung adenocarcinomas. Eleven patients had a new diagnosis of multiple adenocarcinomas in the same lobe (n = 5) or diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 50 publications
3
37
0
Order By: Relevance
“…Finally, the number of targeted genes in our NGS panel may be relatively small. Recent studies on mutational analysis using NGS have included a larger number of targeted genes than we did . Begg et al indicated that at least 20 markers are required from a statistical perspective to distinguish between clonal and independent tumors with high accuracy .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Finally, the number of targeted genes in our NGS panel may be relatively small. Recent studies on mutational analysis using NGS have included a larger number of targeted genes than we did . Begg et al indicated that at least 20 markers are required from a statistical perspective to distinguish between clonal and independent tumors with high accuracy .…”
Section: Discussionmentioning
confidence: 93%
“…With the advances in high‐throughput sequencing technologies, mutational analysis for specific driver and suppressor genes has been shown to be useful for distinguishing between multiple primary tumors and pulmonary metastases . In recent years, in patients with MLC, several reports have been published of mutational analyses by NGS, which allows analysis for multiple gene mutations at once . In this study, we investigated the mutational profiles by NGS of 20 lung cancer‐related genes in surgically resected paired tumors obtained from the same patients and compared the clinicopathological diagnoses with the diagnoses based on mutational evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, next‐generation sequencing assays for the detection of genomic alterations with therapeutic, diagnostic, and prognostic significance in lung cancer have been routinely utilized in major medical centers. Saab et al reviewed 18 patients with a total of 52 lung adenocarcinomas to evaluate the efficacy of comprehensive histopathological evaluation supplemented with molecular analysis using next‐generation sequencing . The combined morphological and genomic data approach proved to be of significant value and achieved a conclusive diagnosis in 94% of the patients tested.…”
Section: Discussionmentioning
confidence: 99%